2018
DOI: 10.1149/2.0651816jes
|View full text |Cite
|
Sign up to set email alerts
|

The Hydrogen-Bonded Ferrocenylmethanol: Mediation of Electron Transfer for Physically Adsorbed Glucose Oxidase

Abstract: The mechanism of electron transfer of ferrocenylmethanol through the self-assembled monolayer (SAM) of mercaptosuccinic acid (MSA) on gold was investigated. A key finding is that the hydrogen-bonded FcMeOH plays the role of a mediator in the electron transfer involving the physically adsorbed glucose oxidase at the MSA SAM surface. The space-conformation of the hydrogenbonding between FcMeOH and MSA was obtained by computational methods. The FcMeOH interacts with MSA via the strong hydrogen bond with the short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This phenomenon is similar to that observed for the artificial model liquors, suggesting that the CV peak potentials are correlated to the alcohol content in the liquors. In consideration of the intermolecular interactions, we further optimized the conformation of FcCH 2 OH and C 2 H 5 OH by computational methods 20 (Calculations using density functional theory). As seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This phenomenon is similar to that observed for the artificial model liquors, suggesting that the CV peak potentials are correlated to the alcohol content in the liquors. In consideration of the intermolecular interactions, we further optimized the conformation of FcCH 2 OH and C 2 H 5 OH by computational methods 20 (Calculations using density functional theory). As seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3c, an H-bonding interaction between the O atom of C 2 H 5 OH and the H atom of FcCH 2 OH was observed, which was similar to the previous reports. 20 Julian Vrbancich et al have demonstrated that the positive charge of the oxidized form (Fc + CH 2 OH) locates at the iron atom of the ferrocene ring, 28 thus it can be suggested that the net positive charge on iron atom will not affect the H-bonding between the H atom of Fc + CH 2 OH and the O atom of C 2 H 5 OH, due to the large distance between the H-bond and the positively charged iron. Therefore, it is reasonable to suggest that the H-bonding interaction between C 2 H 5 OH and the reduced form (FcCH 2 OH) is nearly equal to that between C 2 H 5 OH and the oxidized form (Fc + CH 2 OH).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation